The effect of sediment loading in Fennoscandia and the Barents Sea during the last glacial cycle on glacial isostatic adjustment observations - W. van der Wal; T. IJpelaar (Solid Earth, 2017)
Models for glacial isostatic adjustment (GIA) routinely include the effects of meltwater redistribution and changes in topography and coastlines. Since the sediment transport related to the dynamics of ice sheets may be comparable to that of sea level rise in terms of surface pressure, the loading effect of sediment deposition could cause measurable ongoing viscous readjustment. Here, we study the loading effect of glacially induced sediment redistribution (GISR) related to the Weichselian ice sheet in Fennoscandia and the Barents Sea. The surface loading effect and its effect on the gravitational potential is modeled by including changes in sediment thickness in the sea level equation following the method of Dalca et al. (2013). Sediment displacement estimates are estimated in two different ways: (i) from a compilation of studies on local features (trough mouth fans, large-scale failures, and basin flux) and (ii) from output of a coupled ice–sediment model. To account for uncertainty in Earth's rheology, three viscosity profiles are used. It is found that sediment transport can lead to changes in relative sea level of up to 2 m in the last 6000 years and larger effects occurring earlier in the deglaciation. This magnitude is below the error level of most of the relative sea level data because those data are sparse and errors increase with length of time before present. The effect on present-day uplift rates reaches a few tenths of millimeters per year in large parts of Norway and Sweden, which is around the measurement error of long-term GNSS (global navigation satellite system) monitoring networks. The maximum effect on present-day gravity rates as measured by the GRACE (Gravity Recovery and Climate Experiment) satellite mission is up to tenths of microgal per year, which is larger than the measurement error but below other error sources. Since GISR causes systematic uplift in most of mainland Scandinavia, including GISR in GIA models would improve the interpretation of GNSS and GRACE observations there.